Evaluation of the utilization rate of e-services provided by the local administration in Lubelskie Voivodeship - Ziętek, Daniel; Miłosz, Elżbieta (Journal of Computer Sciences Institute, 2017)
Local Administration Entities of Lubelskie Voivodeship have access to systems and tools allowing for creating, implementing and providing access to e-services. Thus, they should make these services available to citizens and entrepreneurs, update them on a regular basis and improve their maturity level. This article presents results of research, including evaluation of the utilization rate of e-services provided by the local administration in Lubelskie Voivodeship